Pengembangan Media Pembelajaran Bahasa Arab Berbasis Kartu Ahad Dalam Pelajaran Mufradhat Untuk Siswa Kelas 7 - Suci Mutiara Fitriah (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2023)
Abstract: Development Media Learning Arab Language Based Ahad Card In Mufradhat Lesson For 7th Grade Student High SchoolThis research was conducted to obtain the results of the validity of developing a flash card-based learning media, namely Sunday cards, this media was created to make it easier for students to memorize vocabulary in Arabic (mufradhat). This research was conducted using a descriptive quantitative approach to obtain the results of the validity of the learning media. This study uses the development model of the ADDIE model which consists of 5 stages, the first stage of analysis (Analyze), the design stage (Design), the development stage (Development), the implementation stage (Implemtation), and finally the evaluation stage (Evaluation). Through this stage it can produce a learning media product in the form of Sunday cards, this media will be used to help students memorize Arabic vocabulary, especially in 7th Grade students of Darul Muqamah Junior High School.Abstract: Pengembangan Media Pembelajaran Bahasa Arab Berbasis Kartu Ahad Dalam Pelajaran Mufradhat Untuk Siswa Kelas 7Penelitian ini dilakukan untuk memperoleh hasil kevalidan dari pengembangan suatu media pembelajaran berbasis flash card yaitu kartu ahad, media ini diciptakan untuk mempermudah peserta didik dalam menghafal kosa kata dalam bahasa Arab (mufradhat). Penelitian ini dilakukan menggunakan pendekatan kuantitatif deskriptif untuk memperoleh hasil kevalidan dari media pembelajaran tersebut. Penelitian ini menggunakan model pengembangan dari model ADDIE yang terdiridari 5 tahapan, tahap pertama analisis (Analyze), tahap desain (Design), tahap pengembangan (Development), tahap penerapan (Implemtation), dan yang terakhir tahap evaluasi (Evaluation). Melalui tahap ini dapat menghasilkan suatu produk media pembelajaran yang berupa kartu Ahad, media tersebut akan digunakan untuk membantu peserta didik dalam menghafal kosa kata bahasa Arab khususnya di sekolah SMP Darul Muqamah siswa kelas VII